Bonaventure's aesthetics the delight of the soul in its ascent into God - McKenna, Thomas J. (Thomas Jefferson), 1965- (Lexington Books, 2020)
"Bonaventure's Aesthetics: The Delight of the Soul in Its Ascent into God provides an extensive analysis of Bonaventure's concept of beauty, the first to appear since Balthasar's Herrlichkeit, and the role it plays in the Itinerarium mentis in Deum"--